Using Scalable Vector Graphics (SVG) and Google Sheets to Build a Visual Tool Location Web App - Jonathan Bradley (Code4Lib Journal)
At the University Libraries at Virginia Tech, we recently built a visual kiosk web app for helping patrons in our makerspace locate the tools they need and assist our staff in returning and inventorying our large selection of tools, machines, and consumables. The app is built in Svelte, and uses the Google Sheets "publish to web as csv" feature to pull data from a staff-maintained list of equipment in the space. All of this is tied to a Scalable Vector Graphics (SVG) file that is controlled by JavaScript and CSS to provide an interactive map of our shelving and storage locations, highlighting bins as patrons select specific equipment from a searchable list on the kiosk, complete with photos of each piece of equipment. In this article, you will learn why the app was made, the problems it has solved, why certain technologies were used and others weren't, the challenges that arose during development, and where the project stands to go from here.